The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.2527/jas1987.642507x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Ovulation Rate in Gilts by Increasing Dietary Energy and Administering Insulin during Follicular Growth

Abstract: Two experiments were conducted to examine influences of dietary energy and insulin on ovulation rate and patterns of luteinizing hormone (LH), follicle stimulating hormone (FSH), glucose, insulin and estradiol in gilts during 6 d before estrus. In Exp. 1, 36 gilts were given altrenogest for 14 d to synchronize estrus. In a factorial arrangement, gilts were fed one of two levels of dietary energy (5,771 or 9,960 kcal metabolizable energy (ME)/d), and given one of two levels of porcine insulin (0 or .1 IU/kg bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
4

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(53 citation statements)
references
References 21 publications
1
47
1
4
Order By: Relevance
“…In underfed prepubertal gilts, refeeding increases follicular fluid IGF-I concentrations (Charlton et al, 1993). In cyclic gilts, insulin treatment increases ovulation rate even without a concomitant rise in LH secretion (Cox et al, 1987b (Kirkwood et al, 1988). In cultured porcine granulosa cells, GH enhances the stimulatory effects of oestradiol-17P and FSH on progesterone secretion (Hsu and Hammond, 1987).…”
Section: Ovarian Responsiveness To Gonadotrophinsmentioning
confidence: 99%
“…In underfed prepubertal gilts, refeeding increases follicular fluid IGF-I concentrations (Charlton et al, 1993). In cyclic gilts, insulin treatment increases ovulation rate even without a concomitant rise in LH secretion (Cox et al, 1987b (Kirkwood et al, 1988). In cultured porcine granulosa cells, GH enhances the stimulatory effects of oestradiol-17P and FSH on progesterone secretion (Hsu and Hammond, 1987).…”
Section: Ovarian Responsiveness To Gonadotrophinsmentioning
confidence: 99%
“…Development of follicles and oocytes is improved owing to higher concentrations of insulin (Matamoros et al, 1990;Tokach et al, 1992;van den Brand et al, 1998;Ziecik et al, 2002) or IGF-1 in plasma (Ferguson et al, 2003). The underlying mechanism by which insulin increases follicular development is possibly due to an increase in luteinizing hormone (LH) pulsatility (Cox et al, 1987) or LH production (Adashi et al, 1981), and a higher LH pulse frequency (van den Brand et al, 2000).…”
Section: Energy and Insulin/igf-1mentioning
confidence: 99%
“…Recently, Cox et al (1987) reported that insulin injections during the follicular phase increase ovulation rate, either by a direct effect on ovarian follicle recruitment, or by an effect on the hypothalamo-hypophyseal-ovarian axis. In their reviews, Hughes and Varley (1980) and Aherne and Kirkwood (1985), suggest that the effect of flushing is only in increase ovulation rate to the level that would be obtained if the gilt was maintained on a high level of diet intake.…”
Section: Nutritionmentioning
confidence: 99%